Application of the 'English Grammar' Application in improving student Grammar - Nesa, Nesa; Sari, Puspa; Jusriati, Jusriati (Institut Agama Islam Negeri Palopo, 2023)
In this research, researchers make grammar and applications as the focus of research to improve students' abilities in learning grammar. This study used an experimental method with a quasi-experimental design. Participants in this study were divided into two groups, namely the control group and the experimental group. Based on the data processing, it can be concluded that improving the grammar skills of this English grammar application has a positive impact on improving students' English grammar skills.